Dynamics of stress and mortality for grass dominated ecosystems: an interplay of water limitation, heat, and erosion - Bradfield, Scott J., author; Ocheltree, Troy, advisor; Knapp, Alan, committee member; Augustine, David, committee member; Hoffman, Chad, committee member (Colorado State University. Libraries, 2024)
Grass dominated systems account for ~40% of the earth's terrestrial surface and typically occur in semi-arid and arid regions. The plant species that grow in these systems are known for their ability to withstand disturbance, including drought, grazing, and fire. While it is understood that the plants in these systems often experience multiple forms of stress in a growing season, interactions among these stress variables are not well represented in the literature. In this research, I sought to determine how combinations of stress variables influence the shortgrass steppe, this includes: long-term grazing, drought, erosion, and temperature. Specifically, I examined (1) how the interaction of long-term grazing and drought influences the recovery of the vegetation on the SGS following single-year and multi-year droughts, (2) how the interaction of grazing and erosion influence mortality following exposure to extreme surface temperatures, and (3) performed a comparative analysis of the microclimate of grass dominated systems in the United States to determine the intensity and frequency of stressful abiotic conditions that the vegetation experiences. First, I quantified the interactive effects of single and multi-year droughts with grazing pressure, because the Bouteloua species that dominate the region have been shown to be tolerant of grazing and drought independently, but the interactive effects of the two have not been well studied. Past research has focused on heavy cattle grazing but I included a mixture of moderate cattle grazing with prairie dogs, which is more intensive grazing than heavy cattle grazing. I found that the combined stress of multiple years of drought along with high grazing pressure has the potential to increase mortality in these Bouteloua species. Next, I quantified the erosion severity by ranking the amount crown exposure of the Bouteloua species during a drought on the SGS and then determined how erosion influenced bud outgrowth (production of a tiller) during the recovery year. I combined these data with environmental data collected by the National Ecological Organization Network (NEON) to determine the environmental conditions that the meristems of the plants experienced during the drought. My results showed that the temperatures at the surface of the soil, and exposed meristems, frequently reached levels thought to be lethal to plant cells. I acknowledge that it was likely a combination of water deficit and temperature that led to mortality of Bouteloua species that experienced erosion, but the high temperatures alone had the capacity to cause mortality of the meristems. Finally, I compared several near surface micrometeorological variables of grass dominated systems across the United States. Ultimately, I wanted to determine the frequency that these systems experienced temperatures near the surface that would be damaging to plants, if conventional methods for determining heatwaves represents damaging conditions to grassland plants, and what environmental factors lead to potentially damaging surface temperatures. I found that damaging temperatures occur often at arid sites, conventional heatwaves overestimate heat stress in sites that are wet or at higher latitudes, and underestimates heat stress for arid sites.
Keywords: drought; grazing; bud bank; heat stress; grassland